2021
DOI: 10.3390/ijms221910375
|View full text |Cite
|
Sign up to set email alerts
|

Technological Improvements in the Genetic Diagnosis of Rett Syndrome Spectrum Disorders

Abstract: Rett syndrome (RTT) is a severe neurodevelopmental disorder that constitutes the second most common cause of intellectual disability in females worldwide. In the past few years, the advancements in genetic diagnosis brought by next generation sequencing (NGS), have made it possible to identify more than 90 causative genes for RTT and significantly overlapping phenotypes (RTT spectrum disorders). Therefore, the clinical entity known as RTT is evolving towards a spectrum of overlapping phenotypes with great gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 135 publications
(229 reference statements)
1
1
0
1
Order By: Relevance
“…For KEGG analysis, MECP2 knockdown was related to the dysfunction of PI3K-AKT, TGF-β, Wnt, Hippo signaling and cAMP signaling pathway. Since previous studies suggested that although mutation of MECP2 alters the expression of thousands of genes, the effects of an individual gene are small, indicating MECP2 acts as a global regulator of gene expression and chromatin architecture that mediates cellular changes through mediation of a great number of genes genome-wide [25]. Our organoids transcriptome data was widely mimic the previous ndings.…”
Section: Discussionsupporting
confidence: 82%
“…For KEGG analysis, MECP2 knockdown was related to the dysfunction of PI3K-AKT, TGF-β, Wnt, Hippo signaling and cAMP signaling pathway. Since previous studies suggested that although mutation of MECP2 alters the expression of thousands of genes, the effects of an individual gene are small, indicating MECP2 acts as a global regulator of gene expression and chromatin architecture that mediates cellular changes through mediation of a great number of genes genome-wide [25]. Our organoids transcriptome data was widely mimic the previous ndings.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, our RNA-seq analysis also supported that dysregulated genes in MECP2-KO cortical organoids were enriched in neuron projection guidance, axon guidance, forebrain development and regulation of trans-synaptic signaling, rRNA processing, translational initiation, and P53 signaling pathway. Although mutation of MECP2 alters the expression of thousands of genes, the effects of an individual gene are usually small, indicating MECP2 acts as a global regulator of gene expression and chromatin architecture that mediates cellular changes through mediation of a great number of genes genome-wide [ 46 ]. The present study supports that mutation of MECP2 causes a genome-wide alteration of gene expression during brain organoid development.…”
Section: Discussionmentioning
confidence: 99%
“…Las alteraciones en MECP2 se deben en su gran mayoría a mutaciones puntuales, por lo que el estudio de elección es la secuenciación del gen. Esto puede realizarse en forma aislada o dentro de un panel genético. Un pequeño porcentaje se debe a deleciones o duplicaciones en la secuencia por lo que el estudio para estos casos debiese realizarse con amplificación de sondas dependiente de ligandos múltiples (MLPA, por sus siglas en inglés) 39 . Se han descrito más de 800 mutaciones en MECP2 en pacientes con SR 30 siendo la mayoría puntuales 40,41 .…”
Section: Genéticaunclassified